Faktor Sosiodemografi terhadap Aspek Pengetahuan, Keyakinan, Sikap dan Perilaku Penggunaan Antibiotik pada Masyarakat di Kota Bandar Lampung, Indonesia - Annisa Primadiamanti; Gusti Ayu Rai Saputri; Nurma Suri; Ade Maria Ulfa (Alma Ata University Press, 2026)
Background: Antibiotic resistance (AMR) is a critical global health threat, often exacerbated by inappropriate self-medication. In Indonesia, infectious diseases remain a leading cause of mortality, yet public understanding of and practices regarding antibiotic use are often suboptimal. Objective: This study investigated the association between sociodemographic factors and knowledge, beliefs, attitudes, and practices (KAP) regarding antibiotic use in the community in Bandar Lampung, Indonesia. Methods: A community-based cross-sectional survey was conducted from March to April 2023 across 31 primary healthcare centers in 17 sub-districts. A total of 418 respondents were selected using a two-stage cluster sampling method. Data were collected using a validated questionnaire (Cronbach’s alpha > 0.6) and analyzed using Chi-square and Fisher’s exact tests (p<0.05). Results: The findings showed that 53.35% of respondents had inadequate knowledge, and 49.76% practiced self-medication. Although 94.50% held favorable attitudes toward rational use, a notable